American evangelicals and religious diversity : subcultural education, theological boundaries, and the relativization of tradition - Taylor, Kevin M. (Research in religion and education., 2006)
American Evangelicals and Religious Diversity is a qualitative study of how religion and education intersect at one conservative Christian school. The school is Evangelical and American. The school's curriculum is bible-based and fulfills its state's educational requirements for high school graduation. While the school has an environment that is Evangelical, the students live in a religiously-diverse world. This book documents how three students and their teacher struggle to understand a world that challenges their faith. The context for this understanding is how the teacher presents and the three students come to understand Catholicism, Islam, and the indigenous religions of the Americas. Americans continue to debate whether religious schools are too parochial and do not prepare students to live a diverse society.